Impact of spontaneous rupture on the survival outcomes after liver resection for hepatocellular carcinoma: A propensity matched analysis comparing ruptured versus non-ruptured tumors. Issue 9 (September 2019) - Chua, Darren W.; Koh, Ye-Xin; Allen, John C.; Chan, Chung-Yip; Lee, Ser-Yee; Cheow, Peng-Chung; Jeyaraj, Premaraj; Teo, Jin-Yao; Chow, Pierce K.; Chung, Alexander Y.; Ooi, London L.; Goh, Brian K.P.
Abstract: Introduction: Spontaneous rupture of HCC (srHCC) is a life-threatening sequela of HCC characterized by a high mortality. Liver resection (LR) is the ideal therapeutic strategy as it not only arrests hemorrhage but also remove the offending tumour. We sought to determine the impact of spontaneous rupture on the survival outcomes of patients after LR by performing a propensity score matched (PSM) analysis comparing patients who underwent LR for srHCC versus non-ruptured (nrHCC). Methods: From 2000 to 2015, a total of 67 patients who underwent LR for srHCC which met the study criteria were included. 1:2 PSM was performed comparing 49 of 67 patients with srHCC with 98 nrHCC selected from a cohort of 724 patients who underwent LR during the study period. Results: Median survival following LR for srHCC was 21.9 months, while 5-year overall survival (OS) and disease-free survival (DFS) was 43.1% and 19.4% respectively. After 1:2 PSM analysis, there was no significant difference between LR for srHCC (n = 49) versus nrHCC (n-98) in terms of OS [21.9 (interquartile range (IQR), 11.8–44.0 vs 27.4 (IQR, 6.9–57.8) months, HR 1.02, CI 0.63–1.66, p = 0.94], DFS [11.8 (IQR, 5.6–25.6) vs 13.77 (IQR, 4.5–34.9) HR 0.74, CI 0.54–1.02, p = 0.06] and length of stay [8 (IQR, 7–11) vs 7 (IQR, 6–10) HR 0.93, CI 0.0.68–1.29), p = 0.68]. Conclusion: LR for clinically stable patients with srHCC provides survival and recurrence outcomes that are comparable to patients with nrHCC.